Safety and efficacy of sonothrombolysis for acute ischaemic stroke: a multicentre, double-blind, phase 3, randomised controlled trial - Alexandrov, Andrei V; Köhrmann, Martin; Soinne, Lauri; Tsivgoulis, Georgios; Barreto, Andrew D; Demchuk, Andrew M; Sharma, Vijay K; Mikulik, Robert; Muir, Keith W; Brandt, Gordon; Alleman, John; Grotta, James C; et al. (The Lancet. Neurology, 2019)
BACKGROUND: Pulsed-wave ultrasound increases the exposure of an intracranial thrombus to alteplase (recombinant tissue plasminogen activator), potentially facilitating early reperfusion. We aimed to ascertain if a novel operator-independent transcranial ultrasound device delivering low-power high-frequency ultrasound could improve functional outcome in patients treated with alteplase after acute ischaemic stroke. METHODS: We did a multicentre, double-blind, phase 3, randomised controlled trial (CLOTBUST-ER) at 76 medical centres in 14 countries. We included patients with acute ischaemic stroke (National Institutes of Health Stroke Scale score ≥10) who received intravenous thrombolysis (alteplase bolus) within 3 h of symptom onset in North America and within 4·5 h of symptom onset in all other countries. Participants were randomly allocated (1:1) via an interactive web response system to either active ultrasound (2 MHz pulsed-wave ultrasound for 120 min [sonothrombolysis]; intervention group) or sham ultrasound (control group). Ultrasound was delivered using an operator-independent device, which had to be activated within 30 min of the alteplase bolus. Participants, investigators, and those assessing outcomes were unaware of group assignments. The primary outcome was improvement in the modified Rankin Scale score at 90 days in patients enrolled within 3 h of symptom onset, assessed in the intention-to-treat population as a common odds ratio (cOR) using ordinal logistic regression shift analysis. This trial is registered with ClinicalTrials.gov, number NCT01098981. The trial was stopped early by the funder after the second interim analysis because of futility. FINDINGS: Between August, 2013, and April, 2015, 335 patients were randomly allocated to the intervention group and 341 patients to the control group. Compared with the control group, the adjusted cOR for an improvement in modified Rankin Scale score at 90 days in the intervention group was 1·05 (95% CI 0·77-1·45; p=0·74). 51 (16%) of 317 patients in the intervention group and 44 (13%) of 329 patients in the control group died (unadjusted OR 1·24, 95% CI 0·80-1·92; p=0·37) and 83 (26%) and 79 (24%), respectively, had serious adverse events (1·12, 0·79-1·60; p=0·53). INTERPRETATION: Sonothrombolysis delivered by an operator-independent device to patients treated with alteplase after acute ischaemic stroke was feasible and most likely safe, but no clinical benefit was seen at 90 days. Sonothrombolysis could be further investigated either in randomised trials undertaken in stroke centres that are dependent on patient transfer for endovascular reperfusion therapies or in countries where these treatments cannot yet be offered as the standard of care. FUNDING: Cerevast Therapeutics.
Keywords: trombolytická terapie; kombinovaná terapie; fibrinolytika; výsledek terapie; zbytečná diagnóza a terapie; Male; ultrazvuková terapie; Combined Modality Therapy; Middle Aged; Medical Futility; Fibrinolytic Agents; Ultrasonic Therapy; cévní mozková příhoda; Stroke; Aged; mužské pohlaví; senioři; ischemie mozku; Thrombolytic Therapy; Tissue Plasminogen Activator; dvojitá slepá metoda; Treatment Outcome; tkáňový aktivátor plazminogenu; lidé; ženské pohlaví; Humans; Double-Blind Method; Female; lidé středního věku; Brain Ischemia